Magnetic Properties of the Quadruple Perovskite Oxide CaCu3Fe2Re2O12: Monte Carlo Study. (January 2017) - Arejdal, M.; Jabar, A.; Bahmad, L.; Benyoussef, A.
Abstract: The compound" Quadruple Perovskite OxideCaCu 3 Fe 2 Re 2 O 12 ", composed of the mixed atoms with the magnetic moments Cu(σ = 1/2), Fe(S = 5/2) and Re(q = 1.0), is studied as the aim of this research paper, using Monte Carlo Simulations (MCS). The investigation of this system's magnetic proprieties is made through determining the ground state phase diagrams. The stable phases are determined and discussed, elaborating numerically the partial-total magnetizations. The partial-total magnetic susceptibilities are illustrated as a function of the reduced temperature for determining the critical temperature, and studying the impact of the crystal field on the total magnetization. Then, the analysis of the magnetic hysteresis loops are discussed for different values of the crystal field. The influence of the reduced temperature has been made when investigating the study of our system. Finally, the size system effect is analyzed and discussed for different reduced temperatures. To complete this study, the coercive field has also been elaborated and discussed. Highlights: The ground-state phases have been determined. All the stable phases have been investigated and discussed. The magnetic properties of mixed spins based on Quadruple Perovskite Oxide structure have been investigated. The total magnetizations as a function of the crystal field for the different values of temperature have been established. The hysteresis loop behaviors have been studied and interpreted.